Biochemical and Hormonal Changes Associated with Pregnancy in Barbary Ewes Under Semi-Arid Conditions in Eastern Libya - Bouzeed Boukhazeem; Yaseen Mohammed (AlQalam Journal of Medical and Applied Sciences, 2026)
This study evaluated changes in hematological indices and selected hormonal parameters in Barbary ewes during pregnancy under semi-arid conditions in eastern Libya. Forty clinically healthy ewes were allocated to four groups (n = 10 each): non-pregnant controls and pregnant ewes at the 2nd, 4th, and 5th months of gestation. Blood samples were collected to measure red blood cell count (RBC), white blood cell count (WBC), hemoglobin concentration (Hb), packed cell volume (PCV), and serum insulin and parathormone (PTH). Data were analyzed by one-way ANOVA with Tukey’s post hoc test at p < 0.05. Results: RBC, Hb, and PCV decreased progressively with advancing gestation, whereas WBC increased. Insulin declined significantly from the control group to late gestation, while PTH increased significantly during the same period. The most marked changes were observed in the 4th and 5th months of pregnancy. Conclusion: Pregnancy in Barbary ewes was associated with coordinated hematological and endocrine adjustments, especially in late gestation. These findings indicate altered oxygen-transport indices, enhanced leukocytic activity, modified energy metabolism, and increased calcium regulatory demand. Monitoring these parameters may support better health and nutritional management of pregnant ewes in semi-arid production systems.